Konceptual'noe otnošenie k pogode kak projavlenie nacional'noj mental'nosti - Karapetjan, Natal'ja Grigor'evna (Slavistična revija, 2017)
This article considers the evaluative characteristics of words that Russian-language speakers use to describe the weather by attempting to determine the national specificity of descriptive means forming the concept of "weather." The authors advance a systematization of definitions and epithets pertaining to weather, which might aid in formulating a unified conceptual classification of epithets that aid in understanding the particularities of the Russian community's mentality. The article analyzes different adjectives which Russian native speakers use to describe the weather. The authors offer a systematization of adjectives that refer to the weather and which can help understanding the Russian mentality. The article analyzes assessment word characteristics which Russian's native speakers use to describe the weather. There is an attempt to determine national specific of describing means that generate concept "weather". The authors offer a systematization of definitions and epithets that refers to the weather and can promote creation of a common classification of epithets and help understanding the mentality of Russian society.
Keywords: epitet; jezikoslovje; linguistics; prilastek; Russian; ruščina; vreme; weather